Rekomendasi perencanaan sistem penyaliran pada disposal selatan PT victor dua tiga mega - Putri Lufian Tika; Agus Winarno; Ardhan Ismail; Shalaho Dina Devy; Revia Oktaviani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to analyze the effectiveness of drainage in the southern disposal pit dump 4 area. It uses a descriptive quantitative method with primary data collection in the form of actual channel conditions and dimensions, as well as flow velocity measurements using the float method. Secondary data includes rainfall data, disposal design, topography, and mine progress maps. The analysis uses the Mononobe method to calculate rainfall intensity, the rational method based on a 10-year return period to calculate planned runoff discharge, and the Manning equation to determine channel capacity. The results of this study indicate that the actual open channel in the disposal area of pit dump 4 south has a discharge of 0.50 m3/s under light rain conditions and a discharge of 1.12 m3/s under heavy rain conditions, and experiences a decrease in hydraulic performance due to erosion on the channel walls and sediment deposition at the bottom of the channel. Therefore, the current channel cannot accommodate and drain the maximum discharge that may occur under extreme conditions. It is recommended that an open channel with a channel capacity of 8.45 m3/s can accommodate a planned runoff discharge of 7.68 m3/s, which indicates that the drainage system is capable of accommodating and draining water safely, efficiently, and sustainably